Pengaruh Store Atmosphere dan Harga Terhadap Keputusan Pembelian (Studi Pada Konsumen Palapa Toserba Surabaya) - FEBRIATMOKO, ANJAR (Jurnal Ilmu Manajemen (JIM), 2018)
This study is based on the phenomenon of the gap, the gap is palapa toserba with good store atmosphere and cheap product price but decreasing sales in the last year. The purpose of this study is to analyze and discuss the influence of store atmosphere and price on purchase decisions at palapa toserba.. This study is a conclusive study and using non probability sampling technique. The sampling technique used was judgmental sampling with a total of 220 respondents. Technique of collecting data is using Questionnaire. Scale of measurement in this study using Likert scale. Statistical analysis used is multiple linear regressions analysis with spss. The results of this study indicate that the variable store atmosphere significant effect on purchasing decisions with significant value 0.018. Price variables have significant effect on purchasing decision with significant value 0.000. Keywords: store atmosphere, price, purchase decision.